3. DEPRESSION AND ANXIETY IN PATIENTS WITH PERIPHERAL VASCULAR MALFORMATIONS AT THE UNIVERSITY MEDICAL CENTER HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe socio-demographic and clinical characteristics, and to determine the prevalence of depression and anxiety in patients with peripheral vascular malformations.Subjects and methods: A descriptive cross-sectional study was conducted on 51 patients with peripheral vascular malformations at the University Medical Center Ho Chi Minh city from January 2025 to April 2025, using convenience sampling and the HADS.Results: The median age was 30 years (22-37); females accounted for 62.8%; the prevalence of depression and anxiety was 7.8% and 13.6%, respectively.Conclusions: The prevalence of depression and anxiety in patients with vascular malformations in this study was low. Most patients were female, with lesions predominantly located in the lower limbs and associated with cardiovascular comorbidities. It is necessary to integrate mental health screening for depression and anxiety into treatment strategies for patients with peripheral vascular malformations.
Keywords: Depression; anxiety; peripheral vascular malformations; HADS.